INTERNET USAGE BY COLLEGE STUDENTS AS THE SEARCHING MEDIA AND INFORMATION INVESTIGATION - Iman Murtono Soenhadji; Romdhoni Susiloatmadja (Jurnal Ilmiah Ekonomi Bisnis, 2009)
This  research  aims  to  investigate  internet  utilization among  undergraduate  students (S1) of  Information Systems,  Information Technology, Management, Accounting and D3 degree students of Business and Entrepreneurship.  Extant internet facility in this study  is  utilization  of  University  website  by  the  students  in  accordance  with  their academic grades and assignments given by  the  lecturers. This research also  focuses on determinant and  constraint  factors  in choosing  internet as media  for  information searching  and  browsing. The  respondents  for  this  study  are  students  of Faculty  of Economics  and  Faculty  of  Computer  Science,  Gunadarma  University.    From  1200 targeted respondents, only 41 students respond in the first stage and 140 in the second stage. Questionnaire  is  delivered  using  (download  mode  in)  lecturer  website. Respondents  were  grouped  based  on  the  study  program, Statistical  testing  using SPSS  indicates  that  the  most  frequent  visited  websites  are  education-related  ones, whereas the most searched and browsed websites are the commercial and institutional ones.   The most  exploited menu  in  the University website  is Studentsite. Pearson’s chi-square  test  (with  significance degree =  0.006) denotes a  significant  relationship between study program and students’ confidence level of internet contribution to their study.  Moreover, the levels of students’ confidence vary among program studies.   Keywords:  determinant  factors,  constraint  factors,  internet,  information,  university students, websites.